2018
DOI: 10.1126/scisignal.aan6831
|View full text |Cite
|
Sign up to set email alerts
|

Inactivating mutations in Drosha mediate vascular abnormalities similar to hereditary hemorrhagic telangiectasia

Abstract: The transforming growth factor–β (TGF-β) and bone morphogenetic protein (BMP) family of cytokines critically regulates vascular morphogenesis and homeostasis. Impairment of TGF-β or BMP signaling leads to heritable vascular disorders, including hereditary hemorrhagic telangiectasia (HHT). Drosha, a key enzyme for microRNA (miRNA) biogenesis, also regulates the TGF-β and BMP pathway through interaction with Smads and their joint control of gene expression through miRNAs. We report that mice lacking Drosha in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 47 publications
0
35
0
Order By: Relevance
“…The tissue-specific manifestation of physical abnormalities in DBA suggests a differential susceptibility to ribosome abnormalities or insufficiency of each cell type, presumably due to specific demands on protein synthesis. For example, we found that erythropoiesis is more severely impaired than vascular development in Drosha cKO mice (Jiang et al, 2017;Jiang et al, 2018). We speculate that erythrocyte progenitors, rapidly proliferating with high demand for Gata1 and globin protein synthesis, are more susceptible to ribosome shortages than endothelial cells.…”
Section: Discussionmentioning
confidence: 73%
“…The tissue-specific manifestation of physical abnormalities in DBA suggests a differential susceptibility to ribosome abnormalities or insufficiency of each cell type, presumably due to specific demands on protein synthesis. For example, we found that erythropoiesis is more severely impaired than vascular development in Drosha cKO mice (Jiang et al, 2017;Jiang et al, 2018). We speculate that erythrocyte progenitors, rapidly proliferating with high demand for Gata1 and globin protein synthesis, are more susceptible to ribosome shortages than endothelial cells.…”
Section: Discussionmentioning
confidence: 73%
“…A study by Jiang et al identified a higher prevalence of Drosha mutations in an HHT population and generated robust Drosha knockout animal models. Exome sequencing was performed on a total of 98 individuals; 23 confirmed HHT patients and 75 probands suspected to have HHT who lacked known pathogenic mutations [ 95 ]. Three heterozygous Drosha mutations (P32L, P100L and K226E) were detected in seven of the 98 individuals (~7%) compared with 0.04% in the general population [ 93 ].…”
Section: Mirs As Pathogenic Factors In Hhtmentioning
confidence: 99%
“…An additional Drosha mutant (R279L) was found in a separate HHT family [ 93 ]. These Drosha mutants were analyzed in mouse embryonic fibroblasts (MEFs); interestingly, only the P100L and R279L mutants were shown to reduce expression of specific miRs, by approximately 17% and 35%, respectively, compared to wild type (WT) [ 95 ]. P100L and R279L were introduced into zebrafish embryos to investigate their angiogenic functions.…”
Section: Mirs As Pathogenic Factors In Hhtmentioning
confidence: 99%
See 2 more Smart Citations